Ho Chi Minh City 2000 to 2050: An Annotated Illustration of Social Transformation - Prendergast, Cheryl; Earl, Catherine (Lidé města, 2025)
This innovative visual essay, consisting of six hand-drawn line illustrations and annotations, illustrates half a century of urban development in Ho Chi Minh City, Vietnam’s largest city and a growing mega-urban region. Starting with anthropological documentation of urban life in the year 2000, our work engages with academic literature and speculative futures to map the transformation of the city to 2050. The possibilities we present aim to provoke discussion and reflection, contributing to rethinking policy and practice solutions and reframing a Southeast Asian mega-city in future horizoning.